A STUDY ON THE SKILLS GAP ANALYSIS IN THE JORDANIAN TOURISM SECTOR - Ali S. HYASAT; Giuseppe AMORUSO; Alessandro IANNIELLO (Geo Journal of Tourism and Geosites, 2023)
According to the national development plans, the Jordanian tourism sector needs to be updated in order to meet international qualitative standards. To achieve this goal, one of the expected actions to be undertaken is the definition and the implementation of innovative professional profiles that should be integrated within the whole supply chain, and the updating of the related study plans. In order to address this demand, the research aimed to produce a skills gap analysis of the Jordanian tourism, hospitality, and heritage education system, which should highlight sets of innovative and underdeveloped skills for the tackled sectors, and the relative academic paths. The research also aimed to understand the actual offering of the Jordanian education system and to compare it with the requirements of the labor market. Although different plans have been developed, their implementation is still not fully exploited to achieve the desired transformation of the reference sector. By exploiting mixed research techniques, both quantitative and qualitative, it has been possible to understand the actual offeri ng of the Jordanian education system and to compare it with the requirements of the labor market: these activities represent the needed basis to produce the demanded skills gap analysis, which is also part of this contribution.